Physical Activity to Prevent and Treat Hypertension: A Systematic Review - Pescatello, Linda S; Buchner, David M; Jakicic, John M; Powell, Kenneth E; Kraus, William E; Bloodgood, Bonny; Campbell, Wayne W; Dietz, Sondra; Dipietro, Loretta; George, Stephanie M; Macko, Richard F; McTiernan, Anne; et al. (Medicine and science in sports and exercise, 2019)
This systematic umbrella review examines and updates the evidence on the relationship between physical activity (PA) and blood pressure (BP) presented in the 2008 Physical Activity Guidelines Advisory Committee Scientific Report. We performed a systematic review to identify systematic reviews and meta-analyses involving adults with normal BP, prehypertension, and hypertension published from 2006 to February 2018. In total, 17 meta-analyses and one systematic review with 594,129 adults ≥18 yr qualified. Strong evidence demonstrates: 1) an inverse dose-response relationship between PA and incident hypertension among adults with normal BP; 2) PA reduces the risk of cardiovascular disease (CVD) progression among adults with hypertension; 3) PA reduces BP among adults with normal BP, prehypertension, and hypertension; and 4) the magnitude of the BP response to PA varies by resting BP, with greater benefits among adults with prehypertension than normal BP. Moderate evidence indicates the relationship between resting BP and the magnitude of benefit does not vary by PA type among adults with normal BP, prehypertension, and hypertension. Limited evidence suggests the magnitude of the BP response to PA varies by resting BP among adults with hypertension. Insufficient evidence is available to determine if factors such as sex, age, race/ethnicity, socioeconomic status, and weight status or the frequency, intensity, time, and duration of PA influence the associations between PA and BP. Future research is needed that adheres to standard BP measurement protocols and classification schemes to better understand the influence of PA on the risk of comorbid conditions, health-related quality of life, and CVD progression and mortality; the interactive effects between PA and antihypertensive medication use; and the immediate BP-lowering benefits of PA.